2019
DOI: 10.3390/jcm8010097
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Postoperative Outcomes Following Sugammadex Use in Colorectal Surgery Patients: Retrospective Study

Abstract: Purpose: Sugammadex rapidly reverses muscle relaxation compared to acetylcholinesterase inhibitors. The long-term outcomes of sugammadex, however, are not well known. We compared 30-day postoperative outcomes following sugammadex and acetylcholinesterase inhibitor use in colorectal surgery patients. Patients and methods: Colorectal surgical patients older than 21 were included in this retrospective study, and were dichotomized according to use of reversal agents, sugammadex (group S), and acetylcholinesterase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 32 publications
1
30
2
Order By: Relevance
“…38 Chae et al also reported no differences in 30-day postoperative outcomes after sugammadex and acetylcholinesterase inhibitor use. 39 Thus, our results are in line with previous published studies.…”
Section: Perioperative Medicinesupporting
confidence: 94%
“…38 Chae et al also reported no differences in 30-day postoperative outcomes after sugammadex and acetylcholinesterase inhibitor use. 39 Thus, our results are in line with previous published studies.…”
Section: Perioperative Medicinesupporting
confidence: 94%
“…In this context, few studies have been conducted to investigate the effects of sugammadex on bowel movements [7][8][9][10]. Moreover, only a small number of studies have compared the recovery of intestinal movement in groups administered AChEIs and anticholinergic agents and those administered sugammadex, although the studies were conducted retrospectively [11]. This study, therefore, aimed to evaluate the contribution of sugammadex as a reversal agent to the recovery of gastrointestinal (GI) motility in patients undergoing laparoscopic cholecystectomy compared to the contribution of the combination of pyridostigmine and glycopyrrolate.…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al [ 96 ] revealed that unplanned 30-day readmission after major abdominal surgery decreased with sugammadex use. Chae et al [ 97 ] indicated that reversal with sugammadex decreased the incidence of delayed discharge.…”
Section: Recent Clinical Interests Regarding Sugammadexmentioning
confidence: 99%